Teaching competence in mathematics, science and technology when solving a context problem with the Inca archaeological complex of Raqchi, Cusco - Peru (Revista Innova Educación, 2021)
Competencies in math and science should be developed in teachers to exemplify students. For example, the archaeological complex of Raqchi or temple of the God Weracocha are ruins of the Inca culture. The objective was to find how many inhabitants the Inca citadel of Raqchi housed with mathematical competence, solve problems of quantity and science, investigate through scientific methods in secondary education teachers. The study was qualitative, with a content review and analysis methodology; four teachers from the Canas and Canchis Local Educational Management Unit were formed who solved the problem from virtual collegiate meetings. The result of the first group indicates 7538 inhabitants based on the number of Qolcas and the function of the work camp. The second concerning its military role mentions 5308 inhabitants, and the third on the hypothesis of an Inca temple indicates 291 inhabitants. Concluding that the competencies above were achieved according to the National Curriculum of Peru, autonomy, virtual collegiate work that promoted the continuous training of teachers.
Keywords: science; competition; mathematics; Raqchi